Comparison of primary anastomosis and staged surgery in emergency treatment of complicated Crohn's disease. Issue 12 (8th November 2020) - Liu, Rui Qing; Guo, Dong; Qiao, Shuai Hua; Yin, Yi; Guo, Zhen; Gong, Jian Feng; Li, Yi; Zhu, Wei Ming
Abstract : Objectives: Staged surgery (SS) and primary anastomosis (PA) are alternatives to emergency surgery in Crohn's disease (CD). This study aimed to compare postoperative patient outcomes and medical cost of SS and PA for CD emergencies. Methods: Consecutive patients with CD undergoing emergency surgery between December 1997 and January 2017 in three centers were included. The PA and SS groups were compared regarding patient outcomes including postoperative complications and surgical recurrence, as well as hospitalization costs. Results: Altogether 96 (39.5%) patients underwent an emergency PA, and 147 (60.5%) underwent an emergency SS. The incidence of intra‐abdominal septic complications (IASC) in the PA group was 15.6% compared with 7.5% in the SS group ( P = 0.04). The length of hospitalization was longer (32.36 ± 1.76 d vs 19.33 ± 2.36 d, P <0.01) and the hospitalization cost was higher in the SS group (USD 15 811.1 ± 1697.1 vs USD 8345.3 ± 919.5, P <0.01) than the PA group. SS correlated with a lower surgical recurrence rate than PA (log‐rank test, P = 0.04). Presence of diffuse peritonitis, perforating or colonic disease, decision of operation choice made by a senior consultant and more than two concurrent surgical indications were related to the need for SS in emergencies. Localized peritonitis, body mass index (>18.5 kg/m 2 ) and iatrogenic perforation were significantly associated with a low risk of IASC in the PA group. Conclusion: SS can be performed with limited IASC and low surgical recurrence rates for surgical emergencies in CD, although it increases hospitalization costs and delays discharge. Abstract : This study presents a relatively large cohort of patients undergoing emergency surgery for Crohn's disease. Staged surgery proved to be an effective method for preventing postoperative intra‐abdominal septic complications and surgical recurrence but was limited by its increased cost and prolonged length of hospital stay. Individualized surgical strategies for CD emergencies could be established on the basis of perioperative parameters in order to reduce costs and shorten hospital stay with no effect on postoperative outcomes.